Assessment of Patient Satisfaction With MRI Department Services and Staff in Saudi Hospitals - Alghamdi SA (Risk Management and Healthcare Policy)
Sami A Alghamdi Radiological Sciences Department, College of Applied Medical Sciences, King Saud University, Riyadh, 4545, Saudi ArabiaCorrespondence: Sami A Alghamdi, Email slghamdi1@ksu.edu.saBackground: Patient satisfaction is a key component of healthcare quality and is essential for improving clinical outcomes. This study was conducted to assess patient satisfaction with MRI services across 10 hospitals in Saudi Arabia, focusing on both department services and staff performance.Methods: A cross-sectional survey was conducted from July to August 2024 and involved 496 patients at four private and six public hospitals who underwent MRI scans. A structured questionnaire comprising a five-point Likert scale was used to measure patient satisfaction with MRI department services and staff. The data were analyzed using descriptive statistics, Pearson’s chi-square test, t-tests, and ANOVA.Results: The majority of respondents (51.6% female) were 40– 49 years of age, and 41.1% held a bachelor’s degree. Overall, 92% of patients were either satisfied or very satisfied with MRI department services, particularly with registration efficiency (91.9%) and equipment quality (84.7%). However, satisfaction with waiting times was lower, with 66.1% of patients expressing satisfaction. Regarding MRI staff, 95.9% of patients were either satisfied or very satisfied with the privacy and confidentiality maintained during the procedure. A strong positive correlation (r = 0.76, p < 0.001) was observed between satisfaction with staff and overall MRI services.Conclusion: The patients reported high levels of satisfaction with MRI services, particularly with staff professionalism and facility quality. However, waiting times before MRI scans were identified as requiring improvement, particularly in public hospitals. Addressing this issue while maintaining high service standards can enhance patient satisfaction and overall experience.Keywords: patient satisfaction, MRI services, MRI staff performance, healthcare quality, Saudi Arabia